Product Development In “Monity Jaya Bersama” Smes Using Quality Function Development (QFD) Method - Makkulawu, Andi Ridwan (International Journal of Technology and Education Research, 2023)
South Sulawesi Province has a relatively large number of SMEs, one of which is the Monity Jaya Bersama UKM engaged in Beverage products which have the potential to develop their products. The method used in this study is the Quality Function Development (QFD) method. The purpose of this research is to get the voice of the customer, find out the attributes that need to be improved in order to increase sales and get priority on technical response actions. By using the QFD method, the next process is a House of Quality (HOQ) to describe the relationship between consumer needs and technical response. For the overall analysis using the HOQ, 5 priority technical responses were obtained, namely ensuring the taste of drinks according to standards, increasing package sizes, determining packaging designs, quality and safety of raw materials and product innovation. So the attribute that has the highest value and needs to be improved is "guarantees the taste of the drink according to the standard." With a value of "56.22" with this result, the UKM monity jaya together to make this attribute even more enhanced.